From Battlefield to the Servers: Cyber Warfare and the Conflicts (The Shivapuri Journal, 2025)
Cyber warfare has emerged as a critical component of modern conflicts, influencing national security, military strategy, and global stability. This paper explores the evolution of cyber warfare from intelligence gathering during the Cold War to its current role in geopolitical conflicts. Key tactics include cyberattacks in the form of Distributed Denial of Service (DDoS) attacks, malware, and cyber-espionage, with case studies such as the Stuxnet attack and Russia’s cyber offensives against Ukraine illustrating its impact. The research employs a mixed-method approach, incorporating case study  analysis and qualitative data to assess cyber warfare’s economic, psychological, and strategic consequences. Findings highlight the challenges of global cybersecurity coordination, the increasing sophistication of cyber threats, and the role of artificial intelligence in cyber defence. The study concludes that while cyber warfare has transformed  modern conflicts, current international frameworks remain inadequate in mitigating threats. Strengthening global collaboration, investing in advanced cybersecurity strategies, and developing unified policies are essential to securing the digital battlefield.